Accountability of Financial Management of Electoral Grant Funds (Study at the General Election Commission of North Sulawesi Province) - Raintung, Ferdynand Leopol; Mandagi, Marthinus; Sendouw, Recky H. E. (Technium Social Sciences Journal, 2023)
This study aims to reveal the accountability for the financial management of grant funds for the 2020 North Sulawesi Governor and Deputy Governor Election which is managed by the General Election Commission of North Sulawesi Province. Because in its management, problems were found that there were still a number of Claims for Compensation (TGR) for the utilization of the grant budget. This research uses a qualitative approach, descriptive method. Sources of information consist of Commissioners and the North Sulawesi Provincial General Election Commission financial management team. Data collection through interviews, observation and documentation studies. Data analysis through data reduction, data presentation and conclusions. This study used a qualitative research method with three stages of the data collection process, namely 1) the process of entering the research location, 2) the process at the research location, and 3) the data collection process. Data analysis techniques used are reduction, data presentation, and conclusion. Based on the research results obtained, it can be seen that Accountability for Financial Management of Grants for the 2020 Election of the Governor and Deputy Governor of North Sulawesi has not been carried out efficiently and effectively because there are still leaks as evidenced by the results of internal inspections, in this case the Indonesian KPU Inspectorate. Of the three indicators for measuring accountability used, it is known that this is due to the lack of commitment from all agencies involved in managing this grant to carry out each stage following the Standard Operational Procedure (SOP) that already exists and is known together as a guideline for carrying out tasks. Coupled with the still weak sanctions given for negligence/errors in carrying out tasks/activities, where the sanctions given are only in the form of letters of warning which are often made only to fulfill administration and are not actually conveyed to those concerned.